Distribution of massive sulfide and gold mineralization in the folded part of the Orenburg Urals according to materials aerospace survey - V. N. Sudarikov; A. S. Lisov (Литосфера, 2016)
In the second half of the XX century during the Southern Urals regional geological studies GDP-50, GDP-200/2, GDP-1000/3) widely used materials aerial and satellite imagery. Interpretation of these materials revealed widespread in the region lineaments and ring systems morphostructures. Comparison of materials of aerospace survey with different scale geological maps showed that all deposits and most of the occurrences of copper pyrite ore placed on ring morphostructures area that allows us to consider them as additional search features in planning and carrying out of prospecting works. Manifestations of gold confined to the lineament and fault zones.